Potensi Bendung Irigasi Sebagai Pembangkit Listrik Tenaga Mikrohidro - Taufik, Ahmad (Universitas Harapan Medan, 2024)
Sei Padang Dam is a dam that dams the flow of the Padang River specifically to meet the needs of 3 irrigation areas, namely Paya Lombang, Langgau and Bajayu. Sei Padang Dam is currently only used as an irrigation channel and the potential energy that can be produced is not yet known. This study utilizes dam structures that have been completed such as intake channels, headrace channels, forebays and tailrace channels. This potential analysis was carried out using several methods, such as measuring the head using Google Earth, and using irrigation water discharge data from BWS Wil II Sumatra. The results of the study showed that Sei Padang Dam has a PLTMH potential of 50 kW with a water discharge of 2 m3/second and a water fall height/head reaching 4 meters. The most optimal turbine type is the Archimedes screw turbine type.